2021
DOI: 10.1186/s12891-021-04616-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bone mineral density and fragility fracture risk: a case-control study in Changsha, China

Abstract: Background Fragility fracture is associated with bone mineral density (BMD), and most databases used in related researches are instrument-matched. Little is known about the relationship between BMD and fragility fracture risk of native Chinese, especially using local databases as reference databases. Objective To investigate relationship between BMD and risk of fragility fracture in native China. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For male patients, only a 'possible' trend is noted that East Asian patients measure lower total hip T-scores. Another point noted is that, around the timepoint of a hip fracture, at least for East Asians included in this study, male patients tend to measure higher femoral neck and total hip T-scores than those of female patients (Figure 4) (24,28,29,30,32,33). .…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…For male patients, only a 'possible' trend is noted that East Asian patients measure lower total hip T-scores. Another point noted is that, around the timepoint of a hip fracture, at least for East Asians included in this study, male patients tend to measure higher femoral neck and total hip T-scores than those of female patients (Figure 4) (24,28,29,30,32,33). .…”
mentioning
confidence: 76%
“…For the data in the articles included for analysis, the results are shown in Figure 1 for female patients (24)(25)(26)(27)(28)(29)(30)(31)(32)(33), Figure 2 for male and female patients mixed (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and Figure 3 for male patients (24,(28)(29)(30)32,33,46,47). For the data in Figure 2, females commonly constituted 2/3 of the cases, reflecting that hip fracture prevalence among older women is about double of that among older men.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall femoral neck and total hip T-scores in men with SCI were − 1.3 and − 1.7 lower, respectively, compared with those in community-dwelling adults. Since every 1.0 reduction of the T-score re ects a 1.6-1.7 times increase in fragility fracture risk of the vertebra and both upper and lower limbs 22 , the male SCI population in their rst to third years of injury should be regarded as a high fracture risk group, thus increasing awareness for earlier intervention and management to prevent fragility fracture. Vestergaard et al previously demonstrated that the crude fracture rate of individuals with SCI was 2% per year, which was 2 times higher than that of controls, with an exceedingly higher rate of low-energy fractures 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with osteoporosis receive standardized medical intervention, and BMD is regularly examined using dual-energy X-ray absorptiometry. BMD reflects the effectiveness of any medical intervention and is a well-known parameter for the risk of fragility fracture in these patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%